Exploring and Improving Functional Properties of Underutilised Lupin Seed Coat - Zhong, Liezhou (Curtin University, 2020)
The seed coat of the legume lupin is a by-product of its kernel production. To value-add to this seed coat, its chemical and physiochemical properties were investigated through a genotype × environment study. An extrusion cooking process was then developed and optimised through a two-step response surface design to improve its chemical and physicochemical properties. The results demonstrate that the modified seed coat is a good source of dietary fibre and polyphenols for human food.